"Back Off"! Helicopter Parenting and a Retreat From Marriage Among Emerging Adults. (April 2015) - Willoughby, Brian J.; Hersh, Joshua N.; Padilla-Walker, Laura M.; Nelson, Larry J.
The present study used a sample of 779 unmarried emerging adult college students to test the hypothesis that higher levels of helicopter parenting would be related to less positive marital attitudes. Helicopter parenting entails intense and intrusive involvement by parents under the guise of caring and protection. Using hierarchical multiple regression models, results suggested that helicopter parenting was not associated with the general importance placed on marriage but did influence emerging adults' beliefs about the advantages of being single versus being married and their expected age of marriage. Higher reported helicopter parenting among emerging adults was associated with stronger beliefs that being single held more advantages than being married and an expected delay of eventual marriage. Other results suggested that parental warmth with mothers and fathers was also an important correlate of emerging adults' marital attitudes.